Dosimetric Comparison of Hippocampal Sparing Whole Brain Radiotherapy by Volumetric Modulated Arc Therapy, Linac-based Intensity-modulated Radiation Therapy and 3-D Conformal Radiation Therapy: A Cross-sectional Study - Preeya Vasanthakumari; Snigdha Palakada Pushpan; Anilkumar Karumathil; Seeja Joseph; Kilitoli Chopy; Vishnu Reghu; Roshni Tresa Joe; Nicy Maria Thankachan (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Brain metastases are treated with Whole-Brain Radiotherapy (WBRT) using the 3-D Conformal Radiation Therapy (3DCRT) technique. Attempts have been made to perform dosimetric analysis of WBRT with hippocampal sparing using 3DCRT, Volumetric Modulated Arc Therapy (VMAT), and Linac-based Intensity Modulated Radiation Therapy (linac-based IMRT), anticipating technical challenges during contouring and treatment planning. Aim: To perform a dosimetric analysis and comparison ofhippocampal sparing cranial irradiation by 3DCRT, VMAT, and IMRT treatment plans in brain metastases patients. Materials and Methods: The analytical cross-sectional dosimetric study was conducted from November 2022 to September 2023 at Government Medical College, Kottayam, Kerala, India. Ten patients treated for brain metastases with WBRT using 3DCRT were considered for dosimetric analysis. The Planning Target Volume (PTV) dosimetry and hippocampal dosimetry were studied for all ten patients. The important dosimetric parameters included volume receiving 100% dose, Target Coverage (TC), Homogeneity Index (HI) in PTV dosimetry, the mean hippocampal dose, and maximal hippocampal dose in hippocampal dosimetry. The hippocampus and hippocampal avoidance volume were contoured. Treatment plans for 3DCRT, VMAT, and Linac-based IMRT were generated for each patient’s prescription dose of 30 Gy in 10 fractions. The non-parametric Kruskal-Wallis test was used for data analysis. Results: The mean whole brain Planned Target Volume (PTV) was 1190 cm3. The mean hippocampal avoidance volume was 30 cm3, which occupied 2.5% of the whole brain PTV. The average median dose received by the hippocampus was 30.05 Gy, 17.1 Gy, and 17.5 Gy for 3DCRT, Linac-based IMRT, and VMAT, respectively. The mean dose for the hippocampus was 31.03 Gy, 17.7 Gy, and 17.5 Gy for 3DCRT, Linac-based IMRT, and VMAT, respectively (p<0.001). VMAT offered better hippocampal sparing compared to IMRT and 3DCRT. On average, VMAT offered a 2% improvement, and 3DCRT offered a 5% improvement in TC compared to IMRT. The HI of 3DCRT was 0.09, IMRT 0.199, and VMAT 0.150. Conclusion: VMAT and LINAC-based IMRT permit hippocampal-sparing WBRT with adequate target volume coverage and acceptable homogeneity when compared to 3DCRT plans. Thus, the dosimetric study suggests that modern radiotherapy techniques should be advocated for hippocampal-sparing WBRT.